AGE-ASSOCIATED CHANGES IN MOUSE HEPATOCYTE POLARIZATION. (11th November 2018) - Kang, S; Fu, D; Le Couteur, D; Cogger, V
Abstract: Ageing is associated with increased susceptibility to liver diseases and impaired hepatic function. One important factor in normal liver function is functionally sound hepatocytes, the major metabolic cells of the liver. Hepatocytes are polarized cells and loss of polarization results in accumulation of bile, toxins and metabolites leading to hepatocellular damage. Here we examined whether there are changes in hepatocyte polarization that may contribute to age-related susceptibility to liver disease. Hepatocytes were freshly isolated from C57BL6 male mice aged 3-months and 24-months. Cells were cultured in a collagen sandwich configuration and were observed for 72-hours. Lipid droplet numbers were quantified with lipid droplet staining and polarization was determined by immunofluorescence of tight junctional protein Zonula Occludens-1. In addition, ATP levels were quantified, and expression of mitochondrial proteins were measured by western blot. We found that hepatocytes from 24-month-old mice polarized at a significantly faster rate than 3-month-old mice with more and larger lipid droplets present from the beginning of polarization that persisted after 60-hours where canaliculi formed a network resembling the fully polarized morphology. Whereas, reduction of lipid droplet number was evident after 24-hours in hepatocytes from 3-month-old mice. Despite the increase in polarization rate in hepatocytes from 24-month-old mice, cellular ATP levels were lower and peaked earlier in the time-course with decreased expression of mitochondrial fusion proteins compared to hepatocytes from 3-month-old mice. Our findings suggest there are changes in re-establishment of hepatocyte polarization with age, which may impact susceptibility to liver diseases.